2009
DOI: 10.1007/978-3-540-68618-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Family Iridoviridae: Poor Viral Relations No Longer

Abstract: Members of the family Iridoviridae infect a diverse array of invertebrate and cold-blooded vertebrate hosts and are currently viewed as emerging pathogens of fish and amphibians. Iridovirid replication is unique and involves both nuclear and cytoplasmic compartments, a circularly permuted, terminally redundant genome that, in the case of vertebrate iridoviruses, is also highly methylated, and the efficient shutoff of host macromolecular synthesis. Although initially neglected largely due to the perceived lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
207
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(217 citation statements)
references
References 260 publications
(280 reference statements)
1
207
0
9
Order By: Relevance
“…To determine whether XNC10-dependent iVα6 T-cell deficiency has immunological consequences, we infected F0 transgenic tadpoles (stage 53, 25 d postfertilization) with the ranavirus frog virus 3 (FV3), a natural amphibian pathogen (26). XNC10 deficiency resulted in a marked increase in susceptibility to FV3 infection, especially at early stages of infection, compared with nontransgenic controls of the same parent (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether XNC10-dependent iVα6 T-cell deficiency has immunological consequences, we infected F0 transgenic tadpoles (stage 53, 25 d postfertilization) with the ranavirus frog virus 3 (FV3), a natural amphibian pathogen (26). XNC10 deficiency resulted in a marked increase in susceptibility to FV3 infection, especially at early stages of infection, compared with nontransgenic controls of the same parent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although Xenopus tadpoles are not as resistant to FV3 infection as adults, they do mount antiviral immune responses (26). We previously reported that beta 2 microglobulin (b2m) silencing, which impairs both class Ia and XNCs surface expression, increased susceptibility to FV3 infection in young tadpoles (17).…”
Section: Discussionmentioning
confidence: 99%
“…Frog virus 3 (FV3), the type species of the genus Ranavirus (family Iridoviridae), was isolated more than 50 years ago (Granoff et al, 1966) but not until the beginning of the 1990s was it recognized as the pathogen responsible for high mortality epizootics in fish, amphibians and reptiles (Chinchar et al, 2009;Lesbarrères et al, 2012). In 2008, infection with Ranavirus sp.…”
Section: Introductionmentioning
confidence: 99%
“…became one of only two notifiable diseases of amphibians listed by the World Organization for Animal Health (2013). Ranaviruses have been responsible for mass mortalities in wild and captive frogs and salamanders in north America, Asia, Australia and Europe (Gray et al, 2009), and are currently the focus of intense research (Chinchar et al, 2009). Experimental infections with various species and isolates of ranaviruses have been achieved through intraperitoneal injection (Tweedell & Granoff, 1968;Wolf et al, 1968), immersion in viral suspension via water bath (Brunner et al, 2005;Harp & Petranka, 2006;Cullen & Owens, 2002), exposure of cutaneous wounds to virus (Cunningham et al, 2007) and oral administration (Wolf et al, 1968;Hoverman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Iridoviruses are nucleo-cytoplasmic large DNA viruses (NCLDVs) and contain circularly permutated and terminally redundant double-stranded genomes [1][2][3]. The family Iridoviridae currently contains five genera, including the genera Iridovirus, Chloriridovirus, Lymphocystivirus, Megalocytivirus and Ranavirus [4].…”
mentioning
confidence: 99%